A Multimodal Hand Vein Database and Recognition System - Babalola, Felix Olanrewaju (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Biometric studies over the years have made the usage of physiological traits in human authentication technologies popular around the world. More recent studies in this field have given rise to more reliable, faster and user friendly security systems. One of the relatively new area of this field is hand vein biometrics where vascular patterns of hands are used for human recognition. This has some advantages over other physiological traits such as inherent spoof-proof attribute, lack of occlusion and noninvasiveness. Additionally, vein patterns can be captured from different parts of the hand, which could in turn be used in a multimodal system. Multimodal systems are generally preferred because they ensure a more robust and secure system compared to unimodal frameworks. In general, this study introduced a hand vein database named FYO with multiple hand vein datasets for palm, dorsal and wrist vein for the purpose of implementing hand vein multimodal biometric systems. Subsequently, feature descriptors such as Histogram of Oriented Gradients, Gabor filter and Binarized Statistical Image Features, and Convolutional Neural Network models such as AlexNet, VGG-16, VGG-19 and ResNet-50 are applied to show the efficiency of the proposed methodologies. Varieties of architectures for improving the robustness of hand vein recognition systems in both unimodal and multimodal forms are proposed in this study. Additionally, all experiments performed with the datasets acquired are similarly carried out on datasets from publicly available databases such as Badawi, Bosphorus, PUT, Tongji Contactless Palm Vein database and VERA, while the performances of the proposed systems are effectively compared to similar studies in the field

ÖZ: Yıllar boyunca yapılan biyometrik çalışmalar, insan kimlik doğrulama teknolojilerinde fizyolojik özelliklerin kullanımını dünya çapında popüler hale getirmiştir. Bu alandaki daha yakın tarihli çalışmalar, daha güvenilir, daha hızlı ve kullanıcı dostu güvenlik sistemlerine yol açmıştır. Bu alanın nispeten yeni olan alanlarından biri, ellerin vasküler örüntülerinin insan tanımasında kullanıldığı el damar biyometrisidir. Bunun, doğal sahtekarlığa karşı koruma özelliği, tıkanıklık olmaması ve invaziv olmama gibi diğer fizyolojik özelliklere göre bazı avantajları vardır. Ek olarak, elin farklı bölgelerinden damar desenleri yakalanabilir ve bu da çoklu bir sistemde kullanılabilir. Çok modlu sistemler, tek modlu çerçevelere göre daha sağlam ve güvenli bir sistem sağladıkları için genellikle tercih edilir. Genel olarak, bu çalışma, el damarı için çoklu biyometrik sistemlerini uygulamak amacıyla avuç içi, el sırtı ve bilek damarı için çoklu el damarı veri kümeleriyle FYO adlı bir el damarı veritabanını sunmuştur. Daha sonra, Yönlendirilmiş Gradyanların Histogramı (HOG), Gabor filtresi ve İkili İstatistiksel Görüntü Öznitelikleri (BSIF) gibi öznitelik tanımlayıcıları ve AlexNet, VGG-16, VGG-19 ve ResNet-50 gibi Evrişimli Sinir Ağı (CNN) modelleri uygulanmıştır. Bu çalışmada hem tek modlu hem de çok modlu formlarda el damarı tanıma sistemlerinin sağlamlığını geliştirmek için çeşitli mimariler önerilmiştir. Ek olarak, elde edilen veri setleri ile yapılan tüm deneyler, Badawi, Bosphorus, PUT, Tongji Temassız Avuçiçi Damar veri tabanı ve VERA gibi kamuya açık veri tabanlarından alınan veri kümeleri üzerinde benzer şekilde gerçekleştirilirken, sistemlerin performansı literatürdeki benzer çalışmalarla etkili bir şekilde karşılaştırılmıştır
Doctor of Philosophy in Computer Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2022. Co-Supervisor: Assoc. Prof. Dr. Yıltan Bitirim and Supervisor: Prof. Dr. Önsen Toygar.
Keywords: Thesis Tez; Computer Engineering Department; Biometric identification; Identification--Data processing; Biometry--Classification; Computer Pattern Recognition; Image processing--Pattern recognition systems; Pattern recognition--computer science; Multimodal biometrics; Feature fusion; Hand vein recognition; Dorsal vein; Palm vein; Wrist vein; CNN models; BSIF